Effects of Contact Angle on the Hysteresis Effect of Soil-Water Characteristic Curves during Dry-Wet Cycles - Gaoliang Tao; Ziyue Li; Lisheng Liu; Yangyang Chen; Kai Gu (Advances in Civil Engineering)
The hysteresis characteristics of soil-water characteristic curves (SWCCs) under dry-wet cycling conditions are very important for understanding unsaturated soil properties, so it is crucial to propose an accurate and efficient method for predicting the hysteretic behaviors of SWCCs. To this end, this paper investigates the hysteresis characteristics of SWCCs in the full suction range of seven kinds of Hunan red clay with different initial dry densities by combination of the pressure plate method, the paper filter method, and the saturated salt solution method. It is found that there are, respectively, strong and weak hysteresis zones in the drying and wetting SWCCs under dry-wet cycling conditions. By combining this feature and based on the drying curve, the soil volume and contact angle changes during the drying and wetting processes are employed to predict the hysteretic behaviors of SWCCs. To verify the validity of the prediction method, the predicted curves of the samples with different initial dry densities are compared with the measured curves. The results show that in the strong hysteresis zone, the hysteresis characteristics of the drying and wetting SWCCs are mainly resulted from the changes in the soil pore structure; in the weak hysteresis zone, the hysteresis characteristics are mainly influenced by the changes in the receding and advancing contact angles corresponding to the drying and wetting processes. The Young–Laplace theory is used to transform the changes of contact angle during the drying and wetting processes into the proportional relationship k of matric suction, and the corresponding wetting curve is obtained by smoothing the drying curve. It is found that the prediction effect in the high suction part (the strong hysteresis zone) is better than that in the weak hysteresis zone, which confirms that the hysteresis effect of SWCCs in the high suction part is influenced by the contact angle. Our proposed method can greatly reduce the test period and has a significant practical application value, which provides a new idea for the prediction of SWCCs under dry-wet cycling conditions.